Ag-Cu composite metal aerogel and preparation method and application thereof

By controlling the dosage ratio and reaction sequence of Cu(NO3)2·3H2O and AgNO3, an Ag-Cu composite metal aerogel with fine and uniform particle size was prepared, which solved the problems of large metal particle size and uneven distribution in the existing technology and achieved efficient electrocatalytic CO2 reduction effect.

CN120624860AActive Publication Date: 2025-09-12CENT SOUTH UNIV +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510783753.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2025-09-12
Estimated Expiration
2045-06-12

AI Technical Summary

Technical Problem

Existing composite metal aerogels have problems such as large metal particle size, uneven distribution, and insufficient cavity structure during the electrocatalytic CO2 reduction process, which affects the catalytic activity and efficiency.

Method used

By controlling the dosage ratio and reaction sequence of Cu(NO3)2·3H2O and AgNO3 and combining the use of reducing agents, Ag-Cu composite metal aerogel with fine particles and uniform metal distribution was prepared to form a nanoporous structure.

Benefits of technology

Efficient electrocatalytic CO2 reduction was achieved, with the Faradaic efficiency of CO reaching over 90%, improving catalytic activity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120624860A_ABST
    Figure CN120624860A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aerogel preparation, and discloses Ag-Cu composite metal aerogel as well as a preparation method and application thereof. The method comprises the following steps: in the presence of a solvent I, contacting Cu (NO3) 2.3 H2O with a reducing agent to carry out first reaction to obtain a mixture I; in the presence of a solvent II, contacting the mixture I with AgNO3 to carry out a second reaction to obtain a solid I; and washing the solid I to obtain a solid II, and sequentially carrying out solvent replacement and drying on the solid II to obtain the Ag-Cu composite metal aerogel. The Ag-Cu composite metal aerogel prepared by the method provided by the invention has the characteristics of fine particles and uniform metal distribution, and also has a nano-porous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel preparation, and in particular to an Ag-Cu composite metal aerogel and a preparation method and application thereof. Background Art

[0002] With the acceleration of global industrialization, carbon dioxide (CO2) emissions are increasing, leading to an intensified greenhouse effect and posing a serious threat to the environment and human society. Electrocatalytic CO2 reduction has attracted widespread attention as an effective means of converting CO2 into high-value-added chemicals (such as carbon monoxide, formic acid, and methanol) and clean fuels. This technology not only reduces CO2 emissions but also enables the recycling of carbon resources, which has important economic and environmental implications.

[0003] In the electrocatalytic CO2 process, the performance of the catalyst plays a vital role. At present, common electrocatalysts mainly include precious metal-based catalysts (such as Au, Ag, Pd, etc.), transition metal-based catalysts (such as transition metal oxides, sulfides, nitrides, etc.) and non-metallic-based catalysts (such as carbon-based materials). However, these catalysts have some problems that need to be solved. For example, although precious metal-based catalysts have high catalytic activity and selectivity, their high cost and scarce resources limit their large-scale application; although transition metal-based catalysts have low costs, they often have problems such as insufficient active sites, poor conductivity, and poor stability, resulting in catalytic performance that needs to be improved.

[0004] Aerogels are a new type of nanomaterial with a high specific surface area, low density, and porous structure, showing great application potential in the field of electrocatalysis. Their unique porous structure can provide abundant active sites, promote the transport of reactants and products, and improve the efficiency of catalytic reactions. However, the aerogel materials currently reported for CO2 electrocatalysis still have some defects in structure and performance. On the one hand, existing composite metal aerogels often have problems with large metal particle size and uneven distribution, which leads to insufficient exposure of active sites and affects the activity and selectivity of the catalyst. On the other hand, many aerogels lack an effective cavity structure, which is not conducive to the transport of reactants and electrons, thereby reducing the rate and efficiency of the catalytic reaction.

[0005] At present, although there have been some research reports on the preparation of composite metal aerogels, the specific structural design and preparation methods for optimizing the electrocatalytic CO2 performance still need to be further explored. For example, Jiangsu Sopo Company proposed to grow metal aerogels in situ on a porous conductive support, and obtain self-supporting electrodes through gelation of metal nanoparticle colloidal solutions, solvent exchange and freeze-drying. However, this method has insufficient control over the size and distribution of metal particles, which may lead to limited active site density. In addition, the traditional freeze-drying process may destroy the cavity structure of the aerogel and affect the mass transfer efficiency. The Liu Tianxi research group of Jiangnan University used the salting-out gel method to control the interface ratio of Cu-In metal aerogels and found that aerogels with high Cu / Cu2In interface abundance exhibited a CO Faraday efficiency of 94.5% in CO2 reduction. However, the uniformity of metal particles in its preparation process still needs to be optimized, and the controllability of the cavity structure has not been fully reflected, which may limit the diffusion of reactants and the exposure of active sites. Similarly, the Pt-Ni bundled nanocage aerogel developed by Sun Yat-sen University has a three-dimensional porous network, but its synthesis relies on the precious metal (Pt), which is expensive, and the cavity structure is not specifically designed for CO2 reduction. Therefore, how to achieve the miniaturization and uniform distribution of metal particles through reasonable material design and preparation technology, while constructing an effective nanoporous structure, is a major challenge facing this field.

[0006] In view of this, it is necessary to provide a composite metal aerogel with the advantages of high activity, high stability and low cost, providing a new solution for the industrial application of electrocatalytic CO2 reduction. Summary of the Invention

[0007] The purpose of the present invention is to provide a composite metal aerogel with fine particles, uniform metal distribution and nanoporous structure.

[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing Ag-Cu composite metal aerogel, the method comprising:

[0009] (1) in the presence of solvent I, contacting Cu(NO3)2·3H2O with a reducing agent to perform a first reaction to obtain a mixture I; the conditions of the first reaction at least meet the following conditions: temperature of 5-50°C and time of 1-5 minutes;

[0010] (2) contacting the mixture I with AgNO3 in the presence of a solvent II to perform a second reaction to obtain a solid I;

[0011] (3) washing the solid I to obtain the solid II, performing solvent replacement and drying in sequence to obtain the Ag-Cu composite metal aerogel;

[0012] The molar ratio of the Cu(NO3)2·3H2O, the AgNO3 and the reducing agent is 1:0.50-0.75:1.5-5.

[0013] The second aspect of the present invention provides an Ag-Cu composite metal aerogel prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides a use of the Ag-Cu composite metal aerogel described in the second aspect in the electrocatalytic reduction of CO2.

[0015] The present invention controls the contact sequence of reaction raw materials to produce an appropriate micro-disturbance effect while controlling the usage ratio of the two metals and combining other technical features to synthesize a composite metal aerogel with fine particles, uniform metal distribution and a cavity structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a SEM image of the Ag-Cu composite metal aerogel J1 prepared in Example 1 of the present invention;

[0017] Figure 2 is a SEM image of the Ag-Cu composite metal aerogel J2 prepared in Example 2 of the present invention;

[0018] Figure 3 is a SEM image of the Ag-Cu composite metal aerogel DJ1 prepared in Comparative Example 1 of the present invention;

[0019] Figure 4 is a SEM image of the Ag-Cu composite metal aerogel DJ2 prepared in Comparative Example 2 of the present invention;

[0020] Figure 5 is a SEM image of the final product DJ3 prepared in Comparative Example 3 of the present invention;

[0021] Figure 6 is a SEM image of the final product DJ4 prepared in Comparative Example 4 of the present invention;

[0022] Figure 7 is a SEM image of the Cu metal aerogel DJ7 prepared in Comparative Example 7 of the present invention;

[0023] Figure 8 is a SEM image of the Ag metal aerogel DJ8 prepared in Comparative Example 8 of the present invention;

[0024] Figure 9 is a TEM image of the intermediate product mixture I prepared in Example 1 of the present invention;

[0025] Figure 10is a TEM image of the intermediate product mixture I prepared in Comparative Example 5 of the present invention;

[0026] Figure 11 is a TEM image of the intermediate product mixture I prepared in Comparative Example 6 of the present invention;

[0027] Figure 12 is a TEM image of the Ag-Cu composite metal aerogel J1 prepared in Example 1 of the present invention;

[0028] Figure 13 is a TEM image of the Ag-Cu composite metal aerogel J2 prepared in Example 2 of the present invention;

[0029] Figure 14 : is the Ag and Cu element distribution diagram of the Ag-Cu composite metal aerogel J1 prepared in Example 1 of the present invention;

[0030] Figure 15 3 is a diagram showing the distribution of Ag and Cu elements in the Ag-Cu composite metal aerogel J2 prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0032] As mentioned above, the first aspect of the present invention provides a method for preparing Ag-Cu composite metal aerogel, the method comprising:

[0033] (1) in the presence of solvent I, contacting Cu(NO3)2·3H2O with a reducing agent to perform a first reaction to obtain a mixture I; the conditions of the first reaction at least meet the following conditions: temperature of 5-50°C and time of 1-5 minutes;

[0034] (2) contacting the mixture I with AgNO3 in the presence of a solvent II to perform a second reaction to obtain a solid I;

[0035] (3) washing the solid I to obtain the solid II, performing solvent replacement and drying in sequence to obtain the Ag-Cu composite metal aerogel;

[0036] The molar ratio of the Cu(NO3)2·3H2O, the AgNO3 and the reducing agent is 1:0.50-0.75:1.5-5.

[0037] The inventors of the present invention found that when AgNO3 is first reacted with a reducing agent and then with Cu(NO3)2·3H2O for a second reaction, the nanoparticles adhere to micron-sized blocks and cannot form a three-dimensional network cavity structure; when AgNO3 is first reacted with Cu(NO3)2·3H2O and then with a reducing agent for a second reaction, the sample exhibits a flocculent structure and cannot form a three-dimensional network cavity structure.

[0038] The inventors also discovered that when the molar ratio of Cu(NO₃)₂·3H₂O to AgNO₃ is less than 1:0.50 or greater than 1:0.75, the particle size increases significantly. Furthermore, when the first reaction time is longer than 5 minutes, the particle size also increases with increasing reaction time.

[0039] Preferably, the reducing agent is selected from at least one of NaBH4, KBH4, hydrazine hydrate, methanol, ethyl acetate, and n-hexane.

[0040] According to a preferred embodiment, in step (2), the conditions of the second reaction at least meet the following requirements: temperature of 10-35° C. and time of 0.2-3 h.

[0041] According to another preferred embodiment, in step (3), the solvent replacement conditions at least meet the following requirements: an organic solvent is used, the replacement times are 2-4, the interval time is 1-3 hours, and the temperature is 15-40°C.

[0042] More preferably, the organic solvent is selected from at least one of ethanol, methanol, ethyl acetate and n-hexane.

[0043] According to a particularly preferred embodiment, the drying conditions at least meet the following requirements: a temperature of 70-90° C. and a drying time of 2-4 hours.

[0044] According to another particularly preferred embodiment, both the solvent I and the solvent II are deionized water.

[0045] As mentioned above, the second aspect of the present invention provides an Ag-Cu composite metal aerogel prepared by the method described in the first aspect.

[0046] As mentioned above, the third aspect of the present invention provides a use of the Ag-Cu composite metal aerogel described in the second aspect in the electrocatalytic reduction of CO2.

[0047] Preferably, the Faradaic efficiency of CO obtained by electrocatalytic reduction of CO2 is at least 90%.

[0048] The present invention will be described in detail below through examples.

[0049] In the following examples, unless otherwise specified, all raw materials used were commercially available.

[0050] Example 1

[0051] (1) in the presence of deionized water (solvent I), Cu(NO3)2·3H2O is contacted with NaBH4 (reducing agent) to perform a first reaction to obtain a mixture I;

[0052] The conditions for the first reaction were: temperature 25 °C, time 1 min;

[0053] (2) in the presence of deionized water (solvent II), the mixture I is subjected to a second reaction with AgNO3, and solid-liquid separation is performed to obtain solid I;

[0054] The conditions for the second reaction were: temperature 25°C, time 12 h;

[0055] The molar ratio of Cu(NO3)2·3H2O, AgNO3 and reducing agent is 1:0.50:1.25;

[0056] (3) washing solid I with deionized water five times, and performing solid-liquid separation to obtain solid II; and sequentially performing solvent replacement and drying on solid II;

[0057] The solvent replacement conditions were as follows: using anhydrous ethanol, the number of replacements was 3, the interval time was 2 h, and the temperature was 30°C;

[0058] The drying conditions are: temperature 80°C, time 3h;

[0059] Ag-Cu composite metal aerogel J1 was prepared.

[0060] Example 2

[0061] This example is carried out in a similar manner to Example 1, except that:

[0062] In step (1), the amount of AgNO3 was adjusted so that the molar ratio of Cu(NO3)2·3H2O, AgNO3 and reducing agent was 1:0.75:1.25. The other conditions were the same as those in Example 1 to prepare Ag-Cu composite metal aerogel J2.

[0063] Comparative Example 1

[0064] This comparative example was carried out in a similar manner to Example 1, except that:

[0065] In step (1), the amount of AgNO3 was adjusted so that the molar ratio of Cu(NO3)2·3H2O, AgNO3 and reducing agent was 1:1:1.25. The other conditions were the same as those in Example 1 to prepare Ag-Cu composite metal aerogel DJ1.

[0066] Comparative Example 2

[0067] This comparative example was carried out in a similar manner to Example 1, except that:

[0068] In step (1), the amount of AgNO3 was adjusted so that the molar ratio of Cu(NO3)2·3H2O, AgNO3 and reducing agent was 1:0.05:1.25. The other conditions were the same as those in Example 1 to prepare Ag-Cu composite metal aerogel DJ2.

[0069] Comparative Example 3

[0070] This comparative example was carried out in a similar manner to Example 1, except that:

[0071] The reaction order of Cu(NO3)2·3H2O and AgNO3 was adjusted, and the other conditions were the same as those in Example 1 to prepare product DJ3.

[0072] Comparative Example 4

[0073] This comparative example was carried out in a similar manner to Example 1, except that:

[0074] The reaction order of AgNO3 and the reducing agent was adjusted, and the other conditions were the same as those in Example 1 to prepare the product DJ4.

[0075] Comparative Example 5

[0076] This comparative example was carried out in a similar manner to Example 1, except that:

[0077] In step (1), the time of the first reaction was adjusted to 10 min, and the other conditions were the same as those in Example 1, to obtain Ag-Cu composite metal aerogel DJ5.

[0078] Comparative Example 6

[0079] This comparative example was carried out in a similar manner to Example 1, except that:

[0080] In step (1), the time of the first reaction was adjusted to 30 min, and the other conditions were the same as those in Example 1, to obtain Ag-Cu composite metal aerogel DJ6.

[0081] Comparative Example 7

[0082] This comparative example was carried out in a similar manner to Example 1, except that:

[0083] Step (2) was not performed, and the remaining conditions were the same as those in Example 1 to obtain Cu metal aerogel DJ7.

[0084] Comparative Example 8

[0085] This comparative example was carried out in a similar manner to Example 1, except that:

[0086] Step (2) was omitted, and Cu(NO3)2·3H2O was replaced by an equimolar amount of AgNO3. The remaining conditions were the same as those in Example 1 to obtain Ag metal aerogel DJ8.

[0087] Comparative Example 9

[0088] This comparative example was carried out in a similar manner to Example 1, except that:

[0089] The Cu(NO3)2·3H2O was replaced by an equimolar amount of CuCl2, and the other conditions were the same as those in Example 1 to form an AgCl precipitate.

[0090] Test Case

[0091] The catalytic performance of the aerogels prepared in the examples and comparative examples was tested according to the following method:

[0092] The CO2 electrocatalytic reduction reaction is carried out in a three-electrode system using an H-type electrolytic cell. In this three-electrode system, the working electrode (cathode) is a hydrophobic carbon paper loaded with a catalyst, the mercury-mercuric oxide standard electrode serves as the reference electrode of the electrolysis system, and the graphite rod electrode serves as the counter electrode (anode) of the electrolysis system. The cathode electrolyte is 28 mL of 0.5 M KHCO3 saturated with CO2, and the anolyte is 23 mL of 0.25 M K2CO3. The anode and cathode halves of the H-type electrolytic cell are separated by a Nafion proton exchange membrane. Specifically, as follows:

[0093] First, cyclic voltammetry was performed with a scan rate of 100 mV·s -1 , the voltage range is 0.1V to 1.2V (vs.RHE). Then a linear voltammetric scan is performed with a scan rate of 100mV·s -1, the voltage range is from 0 to -1.1V (vs.RHE). After scanning the two alternately three times, the H-type electrolytic cell is sealed and checked for airtightness. After the above preparations are completed, the chronoamperometry test can be carried out. After each potential test, CO2 gas is introduced into the cathode chamber for 10 minutes under stirring conditions at 500rpm to remove the reduction products produced at the previous potential and re-saturate the electrolyte with CO2. After the chronoamperometry test has been running for at least 30 minutes, the production of gaseous products (mainly H2 and CO) is quantitatively detected by the flame ionization detector (FID) and thermal conductivity detector (TCD) of the gas chromatograph, and high-purity argon is used as the carrier gas.

[0094] Table 1

[0095]

[0096]

[0097] It can be seen from the results in Table 1 that the Ag-Cu composite metal aerogel prepared by the method provided by the present invention has good electrocatalytic reduction of CO2 activity and CO selectivity (higher Faraday efficiency).

[0098] Figures 1-4 、 Figure 7 and Figure 8 The SEM images of the metal aerogels prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 7 and Comparative Example 8 of the present invention are respectively shown. Figure 5 and Figure 6 The following are SEM images of the final products prepared in Comparative Examples 3 and 4 of the present invention respectively. Figure 1 and Figure 2 It can be seen from the figure that the Ag-Cu composite metal aerogel prepared by the method provided by the present invention has small particles, which are 41.0nm and 27.7nm respectively; Figure 3 and Figure 4 It can be seen that when the molar ratio of Cu(NO3)2·3H2O to AgNO3 is not within the range required by the present invention, the particles of the prepared Ag-Cu composite metal aerogel are larger, namely 472.3nm and 299.6nm respectively; Figure 7 and Figure 8 It can be seen that the particle sizes of the synthesized Cu metal aerogel or Ag metal aerogel are also relatively large, which are 65.6nm and 77.0nm respectively. Figure 5 and Figure 6 It can be seen that when the contact sequence of Cu(NO3)2·3H2O, AgNO3 and the reducing agent is not carried out in accordance with the requirements of the present invention, the expected aerogel structure cannot be obtained.

[0099] Figures 9-11 TEM images of the intermediate product mixture I prepared in Example 1, Comparative Example 5, and Comparative Example 6 are shown. As can be seen from the figure, as the first reaction time increases, the particle size of the mixture I gradually increases, reaching 2.2 nm, 5.7 nm, and 6.1 nm, respectively.

[0100] Figure 12 and Figure 13 TEM images of the metal aerogels prepared in Examples 1 and 2 of the present invention are shown. As can be seen from the images, there are many small gaps inside the nanoparticles, which makes the prepared aerogels have better catalytic performance.

[0101] Figure 14 and Figure 15 1 and 2 are element distribution diagrams of the metal aerogels prepared in Example 1 and Example 2 of the present invention, respectively. As can be seen from the diagram, Ag and Cu elements are evenly distributed in the aerogel.

[0102] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. A method for preparing Ag-Cu composite metal aerogel, characterized in that: The method includes: (1) in the presence of solvent I, contacting Cu(NO3)2·3H2O with a reducing agent to perform a first reaction to obtain a mixture I; the conditions of the first reaction at least meet the following conditions: temperature of 5-50°C and time of 1-5 minutes; (2) contacting the mixture I with AgNO3 in the presence of a solvent II to perform a second reaction to obtain a solid I; (3) washing the solid I to obtain the solid II, performing solvent replacement and drying in sequence to obtain the Ag-Cu composite metal aerogel; The molar ratio of the Cu(NO3)2·3H2O, the AgNO3 and the reducing agent is 1:0.50-0.75:1.5-5.

2. The method according to claim 1, wherein In step (1), the reducing agent is selected from at least one of NaBH4, KBH4, hydrazine hydrate, glucose, and hydrogen peroxide.

3. The method according to claim 1 or 2, wherein: In step (2), the conditions of the second reaction at least meet the following requirements: temperature of 10-35° C. and time of 0.2-3 h.

4. The method according to any one of claims 1 to 3, wherein: In step (3), the conditions for the solvent replacement at least meet the following requirements: an organic solvent is used, the number of replacements is 2-4, the interval time is 1-3 hours, and the temperature is 15-40°C.

5. The method according to claim 4, wherein In step (3), the organic solvent is selected from at least one of ethanol, methanol, ethyl acetate and n-hexane.

6. The method according to any one of claims 1 to 5, wherein: In step (3), the drying conditions at least meet the following requirements: temperature of 70-90° C. and time of 2-4 h.

7. The method according to any one of claims 1 to 6, wherein: In step (1) and step (2), the solvent I and the solvent II are both deionized water.

8. Ag-Cu composite metal aerogel prepared by the method according to any one of claims 1 to 7.

9. Use of the Ag-Cu composite metal aerogel according to claim 8 in electrocatalytic reduction of CO2.

10. The use according to claim 9, wherein: The Faradaic efficiency of electrocatalytic reduction of CO2 to CO is at least 90%.

Citation Information

Patent Citations

  • Preparation method and application of nano Ag-Cu-based alloy catalyst

    CN112916866A

  • Cu / Ag nano-catalyst for CO2 electrocatalytic reduction as well as batch preparation method and application of Cu / Ag nano-catalyst

    CN118223044A

  • Catalyst for synthesizing methane by reducing carbon dioxide through electro-catalysis as well as preparation method and application of catalyst

    CN119465257A

  • One-pot preparation method of high-alloying gold-silver alloy aerogel material and application of high-alloying gold-silver alloy aerogel material in electrocatalytic reduction of CO2

    CN120079876A